2023
DOI: 10.1097/mpg.0000000000003728
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Perioperative Costs and Induction Immunosuppression in Pediatric Liver Transplant Recipients

Abstract: Objectives:The objectives of this study was to describe variation in induction regimen, identify predictors of induction immunosuppression (IS) choice, and examine the impact of induction IS regimen on length of stay (LOS) and total perioperative costs in pediatric liver transplant recipients. Methods: We analyzed liver transplant utilization data in the Pediatric Health Information System database. Patients were divided into 3 induction IS groups: (1) steroids only, (2) T-cell depleting antibody (TDA), and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that using steroid-only induction is cost-effective and does not prolong hospital stays compared to antibody-mediated induction, making it a preferable approach in lower-income countries like Sri Lanka. 37 In conclusion, as we initiate the pediatric liver transplantation…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have demonstrated that using steroid-only induction is cost-effective and does not prolong hospital stays compared to antibody-mediated induction, making it a preferable approach in lower-income countries like Sri Lanka. 37 In conclusion, as we initiate the pediatric liver transplantation…”
Section: Discussionmentioning
confidence: 97%
“…Initially, basiliximab was administered at reperfusion, but later shifted to Methylprednisolone to minimize the risk of infections. Previous studies have demonstrated that using steroid‐only induction is cost‐effective and does not prolong hospital stays compared to antibody‐mediated induction, making it a preferable approach in lower‐income countries like Sri Lanka 37 …”
Section: Discussionmentioning
confidence: 99%
“…[40] The paucity of practice standards in crucial phases of pediatric transplant care, like ICU course and immunosuppression induction, could contribute to differences in resource utilization, which, in turn, impact cost. [18] Ultimately, a nuanced understanding of the relationship between transplant costs and outcomes is fundamental to defining value in pediatric LT and refining practice guidelines accordingly. While standardization of care may not mitigate the impact of preexisting morbidity, robust peritransplant practice guidelines may be a potential way to reduce unnecessary variation in resource use, unearth previously understudied comorbidities, and promote high-value care.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Notably, this life-saving intervention is resource-intensive and subject to center-specific variation in practice, cost, and outcomes. [15][16][17][18] Thus, there is a need to identify and disseminate best practices from high-performing centers to streamline care and reduce cost. This work is especially relevant to pediatric LT centers since they are under the same regulatory purview as adult centers, thereby facing intense pressure to optimize outcomes and finances across a lower patient volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation